3D SEISMIC EVALUATION OF THE HYDROCARBON POTENTIAL OF STRATIGRAPHIC TRAPS IN X-BLOCK, PENYU BASIN - NIK MOHD HASSAN, NIK NUR ANIS AMALINA (2020)
Penyu Basin is an intra-cratonic basin on northern Sunda Shelf, formed during Oligocene. Oil was discovered in X-Block of Penyu Basin, proving the existence of a working kitchen. X-Block was relinquished in 2006 as it failed to make a commercial discovery. X-Block consists of monocline structure that does not provide effective trapping mechanism. The basement is highly faulted and hard to define. Three wells are drilled in this block targeted on structural traps, with one oil discovery. Despite this, no dedicated exploratory drilling of stratigraphic traps conducted.